2009
DOI: 10.1002/jbm.a.32534
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the bioactive factors preserved in porcine small intestinal submucosa through cellular biological approaches

Abstract: The objective of this study was to develop cellular biological approaches to evaluate the potential effect of bioactive factors in porcine small intestinal submucosa (SIS) on bladder regeneration and angiogenesis. For this purpose, we cultured human bladder smooth muscle cell (HBSMC) and human umbilical vein endothelial cell (HUVEC), and then used cellular biological techniques to characterize in vitro biological effect of SIS components on HBSMC and HUVEC. Our results indicated that the SIS components had sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 44 publications
(109 reference statements)
1
22
0
Order By: Relevance
“…These peptides were found to display chemoattractant potential for several cell types in vitro and in vivo, including endothelial cells and multipotential progenitor cells that participate in the remodeling of the ECM. [70][71][72] However, extensive production of anti-non gal antibodies in response to various immunogenic ECM proteins and proteoglycans may result in binding of these antibodies to the ECM implant and accelerate its destruction by macrophages binding to such antibodies complexed with ECM molecules. This will result in hindering stem cell/ECM interaction, elimination of the implant and possibly in the default process of fibrosis, rather than appropriate remodeling and regeneration of the ECM.…”
Section: Human Anti-non Gal Antibody Response To Mammalian Implant Prmentioning
confidence: 99%
“…These peptides were found to display chemoattractant potential for several cell types in vitro and in vivo, including endothelial cells and multipotential progenitor cells that participate in the remodeling of the ECM. [70][71][72] However, extensive production of anti-non gal antibodies in response to various immunogenic ECM proteins and proteoglycans may result in binding of these antibodies to the ECM implant and accelerate its destruction by macrophages binding to such antibodies complexed with ECM molecules. This will result in hindering stem cell/ECM interaction, elimination of the implant and possibly in the default process of fibrosis, rather than appropriate remodeling and regeneration of the ECM.…”
Section: Human Anti-non Gal Antibody Response To Mammalian Implant Prmentioning
confidence: 99%
“…observed that SIS can stimulate bladder smooth muscle cells and human umbilical vein endothelial cells to attach, proliferate and migrate in vitro . [31] Li et al . showed that small molecular weight peptides released by SIS are biologically active with respect to recruitment of murine endothelial cells in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…SIS possesses a mixture of bioactive factors including cell adhesion factors, mitogenic factors, chemotactic cytokines, and angiogenic factors [10]. In 1966, it was first clinically used for replacement of the inferior vena cava [24].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine-derived small intestinal submucosa (SIS) is one such decellularized, collagen-rich bioscaffold. It has been reported to contain functional growth factors considered vital for tissue restoration [7][8][9] and to preserve a mixture of bioactive factors including cell adhesion factors, mitogenic factors, chemotactic cytokines, and angiogenic factors [8,10]. Several reports have described the utility of SIS in intestinal tissue engineering using animal models [11][12][13][14][15][16].…”
mentioning
confidence: 96%